1988
DOI: 10.1093/ptj/68.3.328
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Transcutaneous Electrical Nerve Stimulation at Auricular Points on Experimental Cutaneous Pain Threshold

Abstract: The purposes of this study were 1) to examine the effect of high intensity, low frequency transcutaneous electrical nerve stimulation at auricular acupuncture points on experimental pain threshold measured at the wrist and 2) to determine the changes in effect over time. Forty-four healthy adult men and women were assigned randomly to one of three treatment groups. Group 1 (n = 15) received TENS to appropriate auricular points for wrist pain, Group 2 (n = 14) received TENS to inappropriate (placebo) auricular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

1989
1989
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 17 publications
0
14
0
Order By: Relevance
“…Patients were instructed to respond verbally to the increasing intensity by saying “Feel it,” to indicate that they felt the electrical stimulus, and by saying “Stop” when they felt pain, at which time the intensity was not increased further. The treatment techniques and parameters were devised with reference to those used in previous studies [14, 18, 34]. Patients in the control group did not receive any auricular TENS and were instructed to rest in bed for 20 minutes.…”
Section: Methodsmentioning
confidence: 99%
“…Patients were instructed to respond verbally to the increasing intensity by saying “Feel it,” to indicate that they felt the electrical stimulus, and by saying “Stop” when they felt pain, at which time the intensity was not increased further. The treatment techniques and parameters were devised with reference to those used in previous studies [14, 18, 34]. Patients in the control group did not receive any auricular TENS and were instructed to rest in bed for 20 minutes.…”
Section: Methodsmentioning
confidence: 99%
“…Recent studies indicate that stimulating acupuncture points as a treatment for pain may be even more effective than TENS on other somatic points. 10,18,19 With respect to this study, the gate control theory best represents the affect of TENS on patients with burn pruritus. The exogenous stimulus provided by TENS appeared to override the patients' perception of pruritus.…”
Section: Discussionmentioning
confidence: 99%
“…1). These auricular points were the same as those used in studies by Oliveri et al, 8 Krause et al, 9 and Noling et al, 10 which resulted in elevated experimental pain threshold at the wrist. In the Somatic Group (n = 17), unilateral TENS was applied to four somatic points: 1) Waiguan (SJ 5), 2) Yangchi (SJ 4), 3) Yangxi (LI 5), and 4) Hegu (LI 4) ( Fig.…”
Section: Methodsmentioning
confidence: 99%
“…67 Stimulation of acupuncture points on the auricle, or auriculotherapy, also is used for pain relief. Studies performed by Oliveri et al, 8 Krause et al, 9 and Noling et al 10 showed that low frequency, high intensity TENS applied to appropriate auricular points increased experimental pain threshold in healthy subjects. These studies indicated that auriculotherapy possibly could decrease pain in patients.…”
mentioning
confidence: 96%